Pengembangan Sistem Manajemen Fasilitas Laboratorium (Studi Kasus: Laboratorium di Jurusan Biologi Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Brawijaya) - Arda Firdaus Ramadhan; Achmad Arwan; Fajar Pradana (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2021)
The laboratory is a place to do practice or research. Department of Biology, Faculty of Mathematics and Natural Sciences, Universitas Brawijaya (FMIPA UB) has 8 laboratories that are used as supporting facilities in the implementation of learning and practicum. Students or lecturers can use laboratory facilities for research by applying for permission to use laboratory facilities according to existing procedures. The problem with current procedures is that researchers must visit each laboratory to obtain laboratory availability information or request permission to use the laboratory. This process is less effective because it takes a lot of time. In addition, recording each research activity still uses paper form so it is difficult to recap the data. To solve this problem, a laboratory facility management system was created. This system can simplify the process of applying for research permits, managing facilities, and recording the use of laboratory facilities. The main stages of system development in this study consist of requirements engineering, modeling, implementation, and testing. System development is carried out using an object-oriented approach. The results of requirements engineering obtained 69 functional requirements and 1 non-functional requirement. In the implementation, the system is developed on a web platform using the model-view-controller (MVC) concept with the Laravel framework. At the testing stage, the results are 100% valid on unit testing, integration, and validation. The results of the compatibility test show that the system can run well on various browsers.